Non-covalently Functionalized Graphene Oxide-Based Coating to Enhance Thermal Stability and Flame Retardancy of PVA Film - Chen, Wenhua; Liu, Pengju; Min, Lizhen; Zhou, Yiming; Liu, Yuan; Wang, Qi; Duan, Wenfeng (Nano-Micro Letters, 2018)
The synergistic effect of conventional flame-retardant elements and graphene has received extensive attention in the development of a new class of flame retardants. Compared to covalent modification, the non-covalent strategy is simpler and expeditious and entirely preserves the original quality of graphene. Thus, non-covalently functionalized graphene oxide (FGO) with a phosphorus–nitrogen compound was successfully prepared via a one-pot process in this study. Polyethyleneimine and FGO were alternatively deposited on the surface of a poly(vinyl alcohol) (PVA) film via layer-by-layer assembly driven by electrostatic interaction, imparting excellent flame retardancy to the coated PVA film. The multilayer FGO-based coating formed a protective shield encapsulating the PVA matrix, effectively blocking the transfer of heat and mass during combustion. The coated PVA has a higher initial decomposition temperature of about 260 °C and a nearly 60% reduction in total heat release than neat PVA does. Our results may have a promising prospect for flame-retardant polymers. Highlights: 1 Functionalized graphene oxide (FGO) containing phosphorus–nitrogen compound was prepared via a non-covalent strategy. 2 The multilayer FGO-based coating was deposited on a poly(vinyl alcohol) (PVA) film using the layer-by-layer assembly technique. 3 A significant synergistic effect between the FTO and conventional flame-retardant elements enhances thermal stability and fire retardancy of the coated PVA film.